Trends on management of superficial venous disease - Ghosh, Shantonu Kumar (International Surgery Journal, 2020)
Venous disease is more common in the society but less addressed than peripheral arterial disease. This is commonest in people who are sedentary workers, people standing for prolonged period, obase. Usually this group of people do not visit a doctor until it restricts him from regular work, ultimately causing a burden in the community. Early diagnosis of venous disease and its’ management is important. Understanding venous pathology, educating people about disease, conducting awareness program among target group of people are essential. Superficial venous disease includes both venous insufficiency and venous thrombosis. Management options of varicose vein and thrombophlebitis are discussed in the presentation.